PEMBERANTASAN SARANG NYAMUK DAN PENYULUHAN PHBS UNTUK MENCEGAH PENYEBARAN PENYAKIT DBD PADA MASYARAKAT DUKUH TEGALMANGU DESA KADOKAN - Muhamad Fikry Abrar Yoga Wardhana; Firhan Ahmad; Shureenzen Suci Syafatillah; Nur Dania Munfaatin Nadilla; Isnaini Tiara Salsabilla; Azida Alfian Utami; Hafidza Aulia Hafsyari; Essa Andaru Anugraheni; Gita Al-Fauzia Salsabilla; Inasya Safira Ramadiani Putri Adi; Ummi Solikhah; Dyah Intan Puspitasari; Ekan Faozi (Jurnal Berkawan: Jurnal Pengabdian kepada Masyarakat, 2026)
Dengue Hemorrhagic Fever (DHF) is an acute febrile illness caused by infection with the Dengue Virus (DENV) and transmitted by Aedes aegypti mosquitoes. This disease is one of the most prevalent tropical diseases affecting humans. In Kadokan Village, DHF ranks as the leading public health concern due to the high number of cases, particularly in Tegalmangu Hamlet. This condition is closely associated with the community’s low awareness of the importance of Clean and Healthy Living Behavior (PHBS) in preventing the spread of DHF. This study aims to enhance community knowledge and awareness regarding the prevention and management of DHF through Mosquito Breeding Site Eradication (PSN) and the implementation of PHBS. The methods employed include observation, health education sessions, and the administration of pre-test and post-test questionnaires to assess the level of knowledge. The observational findings indicate behavioral changes related to environmental cleanliness, while the pre-and post-test results show a significance value of 0.012 (p<0.05), indicating a statistically significant difference in community knowledge before and after the educational intervention on DHF and PHBS.